The effects of preventive aerobics mix on body composition in healthy adult women - Špirtović, Omer; Čaprić, Ilma; Stanković, Mima; Đorđević, Dušan; Murić, Benin; Kahrović, Izet; Mujanović, Rifat; Mekić, Raid; Katanić, Borko; Jelaska, Igor; Sporiš, Goran (Frontiers in Physiology, 2023)
The aim of this research has been to determine the influence of twelve-weeks preventive program Aerobics Mix onto the parameters of a body composition in healthy adult women. The research has been performed in the sample of 64 women examinees and it is divided into two groups, an experimental group (E), made of 34 women examinees (age 32±1,8 year), and control one (K), made of 30 women examinees (age 33±0,5 year). For the assessment of a body, the following measures have been used: a body height, body weight, body fat percentage, muscle mass percentage, skinfold– back (KNL), skinfold– upper arm (KNN), skinfold– stomach (KNT), skinfold– thigh (KNNK). After Mix Aerobics realization, within the women Experimental group, there is reduction of a body mass for -2,5%, waist size for-3,39%, while muscle mass is increased for 2,26%. With all skinfolds within the examinees of E group, there is a statistically gained important reduction of (p<0,05) at the final measuring, compared with the initial one (upper arm -21,10%, stomach -14,36%, back -20,58% and upper leg -13,98%). The reduction of a body mass percentage has been -10,59%, and of BMI -2,5%. Based on the gained results, it can be concluded for the Mix program to be efficient in reduction of the subcutaneous fat tissue and visceral fat, and also to be influential in the increase of a muscle mass.